Exogenous Application of Amino Acids Mitigates the Deleterious Effects of Salt Stress on Soybean Plants - Peña Calzada, Kolima [UNESP]; Olivera Viciedo, Dilier; Habermann, Eduardo; Calero Hurtado, Alexander [UNESP]; Lupino Gratão, Priscila [UNESP]; De Mello Prado, Renato [UNESP]; Lata-Tenesaca, Luis Felipe; Martinez, Carlos Alberto; Ajila Celi, Gabriela Eugenia [UNESP]; Rodríguez, Juan Carlos (MDPI, 2022)
The cultivated area of soybean has increased worldwide in past decades, including regions with saline soils, strongly decreasing growth and productivity. The use of amino acids (AAs) as buffering compounds against stressful conditions can be a useful strategy to mitigate salt stress in these regions. This study aimed to evaluate the effects of foliar application of AA mixtures on the growth, physiology, and biochemistry traits of salt-stressed soybean plants. A pot experiment was designed as a factorial scheme (4 × 3) in a randomized complete design (RCD). Treatments consisted of four concentrations of AA mixtures of a non-VA application, 0.4 mL L−1, 0.8 mL L−1, and 1.2 mL L−1 (VIUSID Agro® (VA) source), which were combined with non-salt stressed and salt-stressed groups (50 and 100 mmol L−1 NaCl), to analyze improvement in growth and potassium (K+) accumulation, maintenance of relative water content (RWC), net photosynthesis rate (A), transpiration (E), stomatal conductance (gs), and chlorophyll content, and increase of proline accumulation and water use efficiency (iWUE). Moderate and high salinity induced a notable increase in oxidative and ionic biomarkers, coupled with higher Malondialdehyde (MDA) concentration and Na+ accumulation. Alternatively, soybean growth, K+ accumulation, and physiological and biochemical parameters were decreased under salinity. Foliar spraying of AAs drastically increased osmolyte accumulation associated with sustained iWUE and RWC, increased proline accumulation, and improved A, E, gs, and chlorophyll content. Greater outcomes were achieved with the foliar spraying of amino acids at 1.2 mL L−1. Collectively, foliar application of AA mixtures plays an important role in salt stress remediation by modifying important physiological and biochemical processes, thereby resulting in a higher growth of soybean plants.
Keywords: abiotic stress; attenuation compounds; foliar application; Glycine max; salinity; Viusid agro